Cryopreservation of Shoot Tips of Valeriana jatamansi, a High Value Threatened Medicinal Plant of India - Gowthami, Ravi; Chander, Subhash; Agrawal, Anuradha; Sharma, Neelam; Bhat, Kailash Chandra; Singh, Anju Mahendru (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):292